PENGARUH ZAT PENGATUR TUMBUH ROOTONE-F DAN SUMBER BAHAN STEK TERHADAP PERTUMBUHAN STEK TEMBESU (Fagraea fragrans) DI PT. JORONG BARUTAMA GRESTON KALIMANTAN SELATAN - Damaris Payung; Susilawati Susilawati (Universitas Lambung Mangkurat, 2014)
This research entitled, The Effect of Growth Regulator Substances Rootone-F and Source Material Cuttings Cutting’s Growth Against Tembesu (Fagraea fragrans) at PT. Jorong Barutama Greston South Kalimantan. The research was conducted in Green House PT. Jorong Barutama Greston. The purpose of this study was to determine the percentage of live cuttings tembesu each treatment, determine the effect of growth regulators (Rootone-F) in accelerating the growth of cuttings tembesu and determine the concentration of growth regulators (Rootone-F) most good and appropriate sources of cuttings material for growth tembesu cuttings on each parameter. The research method used was a randomized block design (RAK), which consists of 5 treatments and 3 replications replications each consisting of 10 cuttings. Group and the treatment used is the source material and the concentration of ZPT cuttings. Observations were conducted to produce data AH0 life percentage = 80%, BH3 = 90%, CH0 and CH1 = 80%, the percentage of rooted AH2 and AH3 = 30%, BH1 and BH2 = 50% and CH4 = 60%. Data on the long shoots and treatment group with data analysis calculated F is smaller than F table is not significant. Data on the number of shoots and the treatment group with data analysis calculated F is smaller than F table is not significant. Root length data to the data analysis group F count = 4.751 ≥ F table = 4.458 is significant, while the effect of the treatment showed no significant effect. Data on the number of roots and the treatment group with data analysis calculated F is smaller than F table is not significant. Of the four parameters used concluded that the group of source materials and the provision of cuttings Rootone-F had no effect on the growth of cuttings Tembesu